PENGEMBANGAN DESA WISATA DI DUSUN JANGO DESA JANGO KECAMATAN JANAPERIA KABUPATEN LOMBOK TENGAH - Jumhur Hakim; Saripudin Serip; Satarudin Satarudin (Devote: Jurnal Pengabdian Masyarakat Global, 2025)
Community service in Jango village, Janaperia District, centeral Lombok Regency, The beckground is the potential for religios tourism as the symbol of the Kaaba. Which is managed independently by the community with the Jabal Rahmah Pokdarwis in Jango village. The problem is that the government is still limited. This couses this tourist park to belles than optimal. Method: Activity preparation : conducting a preliminary survey to Jango, Halmet,  Jango Village, the object of community service activities. Coordinating with the Hamlet apparatus and the head of village and KOPDARWIS of Jango village, administrative management (correspondence), Preparation of tools and materials and accomudation Preparation of places for the implementation of FGD (Focus Group Discussier) activity implementation: FGD (focus group discussion) includes: Delivering the purpose of holding Unram community service activities for the development of religios tourism in Jango village Delivering problems and obstacles faced by the Jango Halmet apparatus, Jango Village and KOPDARWIS of Jango village. Risult Lack of involvment of local and central goverments in the involvement of building the Jabal Rahmah tourism park in Jango village. To date, the Rahmah tourism group administrators. Along with the Jango village government and the community. The involvement of capital owners was the first step in establishing standart facilities. The local community donated their land for the Jabal Rahmah Tourism Park.